HAJI SULAWESI SELATAN PADA MASA NEGARA INDONESIA TIMUR (NIT) (1946-1950) - Adil Akbar (Handep: Jurnal Sejarah dan Budaya, 2021)
This article discusses two things. First, the historiography of the pilgrimage in South Sulawesi during the State of East Indonesia. Second, the correlation between rice and copra as commodities had impacts on economic growth in South Sulawesi. The method used in this article was the historical method by analyzing mainly contemporary archives. This study shows that the people in South Sulawesi can perform the pilgrimage due to the economic growth through rice and copra trade activities in this area, at least during the State of East Indonesia in 1946-1950. One of the benchmarks of economic growth is the number of people in South Sulawesi performing the pilgrimage, especially those who come from rice and copra producing areas.